Determining the Scope of Influence of Health Centers in Sulaymaniyah City in 2018 Using Geographic Information Systems - حسين, بيان علي (Sulaimani Journal for Humanities, 2019)
The health centers are important primary health services in the cities, and their distribution in a fair manner by the residential districts makes it easy to access this service by the population. The aim of this study is to focus on the geographic distribution of the health centers in Sulaymaniyah city using geographic information systems ,The health centers in 2018 are 26 and the population for the same year (745687) people, and according to the planning standards in Iraq, each health center serves approximately (10000) people, and thus there is a shortage in the number of health centers about 48-49 in 2018,but 12 centers cannot be counted because they are randomly distributed and they are close to other centers, and out of 132 residential district in the city 108 of them there is no health center according to the data of 2018. According of this study the future need of health center by 2038 are divided in to 3 possibilities Therefore we took into consideration the three possibilities: low, medium and high growth of population in Sulaymaniyah , In the end, I hope that this study is a successful step in the distribution of all necessary services according to the planning criteria in the city of Sulaymaniyah and other areas.